Folklore Musical Traditions as a Component of the Ethno-History of the Ukrainian Danube Region - Bukhnieva, Olena (Journal of Danubian Studies and Research, 2024)
The article is devoted to the historical, social, and artistic values of folk music traditions of the Ukrainian Danube region, its originality and genre-ethnic features. The role, the place of traditions, the significance of folklore in the life of human society is determined, because folklore is the tradition and reality in which a person lives. The scientific understanding of the regularities of the historical and ethno-social development of folk culture, the specifics of the functioning of certain types and genres of folk art in it is defined. It has been proven that folklore is present in the customs, way of activity and behavior of the people, affects the spiritual and moral culture of the ethnic group, shapes its hopes and life direction.